Lake level and climate records of the last 90 ka from the Northern Basin of Lake Van, eastern Turkey - Cagatay, M. N.; Ogretmen, N.; Damci, E.; Stockhecke, M.; Sancar, U.; Eris, K. K.; Ozeren, S. (Pergamon-Elsevier Science Ltd, 2014)
Sedimentary, geochemical and mineralogical analyses of the ICDP cores recovered from the Northern Basin (NB) of Lake Van provide evidence of lake level and climatic changes related to orbital and North Atlantic climate system over the last 90 ka. High lake levels are generally observed during the interglacial and interstadial periods, which are marked by deposition of varved sediments with high total organic carbon (TOC), total inorganic carbon (TIC), low detrital influx (high Ca/F) and high delta O-18 and delta C-13 values of authigenic carbonate. During the glacial and stadial periods of 71-58 ka BP (Marine Isotope Stage 4, MIS4) and end of last glaciation-deglaciation (30-14.5 ka BP; MIS3) relatively low lake levels prevailed, and grey homogeneous to faintly laminated clayey silts were deposited at high sedimentation and low organic productivity rates. Millennial-scale variability of the proxies during 60-30 ka BP (MIS3 is correlated with the Dansgaard -Oeschger (D-O)) and Holocene abrupt climate events in the Atlantic. These events are characterized by laminated sediments, with high TOC, TIC, Ca/Fe, delta O-18 and delta C-13 values. The Lake Van NB records correlate well in the region with the climate records from the lakes Zeribar and Urmia in Iran and the Sofular Cave in NW Anatolia, but are in general in anti-phase to those from the Dead Sea Basin (Lake Lisan) in the Levant. The relatively higher delta O-18 values (0 to -0.4 parts per thousand) for the interglacial and interstadial periods in the Lake Van NB section are due to the higher temperature and seasonality of precipitation and higher evaporation, whereas the lower values (-0.8 to -2 parts per thousand) during the glacial and stadia] periods are caused mainly by relative decrease in both temperature and seasonality of precipitation. The high delta O-18 values (up to 4.2 parts per thousand) during the Younger Dryas, together with the presence of dolomite and low TOC contents, supports evaporative conditions and low lake level. A gradual decrease in the delta O-18 values from an average of 0.4 parts per thousand during the humid early Holocene to an average of 3.5 parts per thousand during the more arid late Holocene suggests an increasing contribution of winter precipitation. The changes in the seasonality of precipitation in eastern Anatolia are probably caused by changes in the temperatures of North Atlantic and Mediterranean and in the strength of Siberian High. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Lake Van; Northern Basin; Multproxy analyses; 90 ka climate records; Lake level; ICDP PaleoVan